Analisis Pendeteksian Fraudulent Financial Statement Menggunakan Beneish M-Score Model Studi Empiris Pada Bank Umum Syariah Di Indonesia Tahun 2020-2021 - Sudarmansyah, Sudarmansyah; Marliyah, Marliyah; Syahbudi, Muhammad (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2023)
Every year, companies publish financial reports that can shows the company's financial condition is good or bad. To know whether Sharia Commercial Banks in Indonesia commit fraudulent report finance in 2020-2021 and analyze the gaps used inThis fraud was researched using the banking sector. Because this sector has many stages in the business process, there are gapsto commit fraud is considered greater than other sectors. This research is descriptive research with a quantitative approach using eight variables Beneish ratio index and M-score based on Beneish's discovery in 1999. The eight variables are DSRI, GMI, AQI, SGI, DEPI, SGAI, LVGI, and TATA, which are used for detection companies that manipulate or commit fraudulent financial statements. The research results show that all sample companies do not do so financial statement fraud, namely PT. BCA Syariah Bank, PT. Mega Bank Sharia, PT. Bank Victoria Syariah, PT. Bank Negara Indonesia Syariah, PT. Bank Rakyat Indonesia Syariah, and PT. Bukopin Sharia Bank. Detection Fraud is carried out by calculating the eight Beneish ratio index variables 10 sample companies and compare them with the industry average value to detect potential fraud.